THE EFFECT OF TYPE OF POLYURETHANE IN THE FINISHING PROCESS ON THE QUALITY OF CAR SEAT LEATHER - Alfiyatul Masruroh; Entien Darmawati; Elis Nurbalia (Politek ATK Yogyakarta Press, 2023)
This study aims to determine the effect of using bright binder polyurethane material in improving the shiny value in the finishing process of upholstery automotive article for car seat covers. The raw material used in finished dyed cowhide or finished leather with thockness of 1,2-1,4 mm with an area 5 sqft. The trial was carried out using 6 sheets of A4 size finish leather (21x29,7 cm) which would be re-fixed pe sheet with a different concentration of polyurethane for each trial. The method of improving the shiny value for upholstery automotive article is re-sprayed (re-fixative) with trial of variations in reducing matt polyurethane and variations is adding bright binder polyurethane to fixative (top coat) formulations, to get the shiny value according to the customer master sample standards, namely 1,1-1,2 GU. the measurement of the shiny value is carried out using a glossmeter. The result obtained are the addition of polyurethane bright binder 2% to get the best result to improve the shiny value of upholstery automotive for car seat covers. These results have met customer standars both form testing using a glossmeter and critical test carried out. The conclusion is that upholstery auutomotive leather has shiny value that meets the customer master sampel standards.